Targeted next-generation sequencing detects rare genetic events in pheochromocytoma and paraganglioma. Issue 8 (15th March 2019) - Ben Aim, Laurène; Pigny, Pascal; Castro-Vega, Luis Jaime; Buffet, Alexandre; Amar, Laurence; Bertherat, Jérôme; Drui, Delphine; Guilhem, Isabelle; Baudin, Eric; Lussey-Lepoutre, Charlotte; Corsini, Carole; Chabrier, Gérard; et al.
Abstract : Background: Knowing the genetic status of patients affected by paragangliomas and pheochromocytomas (PPGL) is important for the guidance of their management and their relatives. Our objective was to improve the diagnostic performances of PPGL genetic testing by next-generation sequencing (NGS). Methods: We developed a custom multigene panel, which includes 17 PPGL genes and is compatible with both germline and tumour DNA screening. The NGS assay was first validated in a retrospective cohort of 201 frozen tumour DNAs and then applied prospectively to 623 DNAs extracted from leucocytes, frozen or paraffin-embedded PPGL tumours. Results: In the retrospective cohort, the sensitivity of the NGS assay was evaluated at 100% for point and indels mutations and 86% for large rearrangements. The mutation rate was re-evaluated from 65% (132/202) to 78% (156/201) after NGS analysis. In the prospective cohort, NGS detected not only germline and somatic mutations but also co-occurring variants and mosaicism. A mutation was identified in 74% of patients for whom both germline and tumour DNA were available. Conclusion: The analysis of 824 DNAs from patients with PPGL demonstrated that NGS assay significantly improves the performances of PPGL genetic testing compared with conventional methods, increasing the rate of identified mutations and identifying rare genetic mechanisms.